The Road Toward Transformative Treatments for Food Allergy - Phelps, Allyssa; Bruton, Kelly; Grydziuszko, Emily; Koenig, Joshua F. E.; Jordana, Manel (Frontiers in Allergy, 2022)
A series of landmark studies have provided conclusive evidence that the early administration of food allergens dramatically prevents the emergence of food allergy. One of the greatest remaining challenges is whether patients with established food allergy can return to health. This challenge is particularly pressing in the case of allergies against peanut, tree nuts, fish, and shellfish which are lifelong in most patients and may elicit severe reactions. The standard of care for food allergy is allergen avoidance and the timely administration of epinephrine upon accidental exposure. Epinephrine, and other therapeutic options like antihistamines provide acute symptom relief but do not target the underlying pathology of the disease. In principle, any transformative treatment for established food allergy would require the restoration of a homeostatic immunological state. This may be attained through either an active, non-harmful immune response (immunological tolerance) or a lack of a harmful immune response (e.g., anergy), such that subsequent exposures to the allergen do not elicit a clinical reaction. Importantly, such a state must persist beyond the course of the treatment and exert its protective effects permanently. In this review, we will discuss the immunological mechanisms that maintain lifelong food allergies and are, consequently, those which must be dismantled or reprogrammed to instate a clinically non-reactive state. Arguably, the restoration of such a state in the context of an established food allergy would require a reprogramming of the immune response against a given food allergen. We will discuss existing and experimental therapeutic strategies to eliminate IgE reactivity and, lastly, will propose outstanding questions to pave the road to the development of novel, transformative therapeutics in food allergy.